Integrating synchronous and asynchronous internet distributed education for maximum effectiveness - Pullen, J. Mark (2006)
Distributed education delivered via the Internet is a growing practice, with most institutions offering at least course websites and many expanding to full course offerings and even degree offerings. There are two schools of thought with regard to delivery mode; the larger group has focused on asynchronous delivery, accessible at any time via web pages and interactive tutorials and quizzes, while a smaller group advocates synchronous delivery where students are online and interact during class time. This paper summarizes the advantages and disadvantages of the two delivery modes and describes our successful and growing experience of more than a decade using an open source synchronous delivery tool blended with a variety of asynchronous capabilities and classroom instruction. We conclude that a synergistic combination of the two modes with in-person instruction, designed to provide maximum flexibility to the student within the constraints of the subject, offers the best support for student learning.